Privatization in the Land of Believers: The political economy of privatization in Pakistan*. (12th January 2018) - MUNIR, KAMAL; NAQVI, NATALYA
Abstract: Despite theoretical justifications and empirical evidence that state-owned enterprises have played an important role in late development, as well as over three decades of evidence that privatization programmes since the 1980s have had mixed results at best, international financial institutions continue prescribing privatization as a panacea for developing countries. Pakistan is an interesting case to understand why privatization is still considered desirable, because it is one of a set of developing countries that have whole-heartedly implemented Washington Consensus policies. In this context, we analyse privatization in two key economic sectors in Pakistan: energy and banking. Using qualitative and quantitative data, we describe the motivations behind these privatizations, the process by which they were carried out, and analyse the post-privatization performance of these organizations and sectors. We find that in both cases (a) the privatizations failed not only with respect to their stated aims, leading to a decline in national productive capabilities, but also had adverse distributional consequences, shifting the rewards to the buyers while the risks and costs remained with the public sector, and (b) the suboptimal outcomes of the privatizations went largely unchallenged aided by a prevalent neoliberal view amongst the country's economic policy makers and intelligentsia. Our analysis sheds new light on the process by which privatization in the absence of a state with the capacity to discipline business interests has enabled these interests to obtain state-sponsored rents without bringing any of the associated benefits for economic development.